(untitled) (International Research Journal of Management and Social Sciences, 2024)
Feminism has inculcated in women the sense to recognise their potential to lead a better life. In this way, a great change and improvement has been added to the social outlook as now we have women contributing their share in its construction. Although, Feminism started off as a political movement but it can be seen an important part of the literature, that is being written all over the world. There has been a lot of research work conducted on feminism and its application to different literary pieces. Khadija Mastoor is a well known Urdu writer and is famously studied from different perspectives. Khadija Mastoor has very skilfully dealt with theme of feminism in the novel Aangan. Within all the political and social issues, we see the female characters of the novel emerging as prominent individuals, each playing their own role and highlighting the aspects of feminism. This particular study is significant as it attempts to evaluate the concept of feminism as presented in Khadija Mastoor’s novel Aangan which is usually dealt as a novel based on partition and its related phenomena. Also, it focuses on how feminism which is considered a western concept is practiced and perceived in writings of Urdu literature, thereby highlighting the worldwide application of the philosophy.